2013
DOI: 10.1371/journal.pone.0078277
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Combined Methodology for Assessing the Total Quality Control of Herbal Medicinal Products – Application to Oleuropein Preparations

Abstract: Oleuropein (OE) is a secoiridoid glycoside, which occurs mostly in the Oleaceae family presenting several pharmacological properties, including antioxidant, cardio-protective, anti-atherogenic effects etc. Based on these findings OE is commercially available, as Herbal Medicinal Product (HMP), claimed for its antioxidant effects. As there are general provisions of the medicine regulating bodies e.g. European Medicines Agency, the quality of the HMP’s must always be demonstrated. Therefore, a novel LC-MS method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Two healthy, male physical education students, aged 21 and 22 years and designated as A and B, respectively, received an olive leaf extract enriched in OE in the morning after an overnight fast. Specifically, they ingested 1200 mg of Benolea® EFLA®943 (in the form of four 300 mg capsules), containing a total of 204.4 mg OE (Lemonakis et al , ) and provided 10 mL of venous blood just before ingestion and every 15 min up to 1 h after ingestion, every 30 min between 1 and 3 h, and every 1 h between 3 and 6 h through an indwelling catheter in the forearm (0, 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3, 4, 5 and 6 h). The subjects were required to avoid intense physical activity and intake of alcohol, medication or nutritional supplements on the previous day.…”
Section: Methodsmentioning
confidence: 99%
“…Two healthy, male physical education students, aged 21 and 22 years and designated as A and B, respectively, received an olive leaf extract enriched in OE in the morning after an overnight fast. Specifically, they ingested 1200 mg of Benolea® EFLA®943 (in the form of four 300 mg capsules), containing a total of 204.4 mg OE (Lemonakis et al , ) and provided 10 mL of venous blood just before ingestion and every 15 min up to 1 h after ingestion, every 30 min between 1 and 3 h, and every 1 h between 3 and 6 h through an indwelling catheter in the forearm (0, 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3, 4, 5 and 6 h). The subjects were required to avoid intense physical activity and intake of alcohol, medication or nutritional supplements on the previous day.…”
Section: Methodsmentioning
confidence: 99%
“…OLE, another dominant constituent of olive oil is proved to have anti-inflammatory activity [26] and antioxidant activity [5]. Studies showed beneficial outcomes in decrease of coronary atherosclerosis and control blood pressure [27] and it was also explored for its antitumor activity [28].…”
Section: Biological Activities Of Evoomentioning
confidence: 99%
“…Pharmacology-based metabolomics has the potential not only to study pharmacological effects of herbal plants and their metabolic action mechanisms [ 23 , 24 ] but also to discriminate plant species of the same genus [ 25 , 26 ] and the same plant species from different cultivation regions [ 27 ]. It was also adopted to assess the holistic quality of herbal medicinal products [ 28 ].…”
Section: Introductionmentioning
confidence: 99%